“And Then One Day, Me and My Husband, We Learned How to Cross the Street”: Hazara Women’s Experiences in Sydney and Yearnings for ‘Home’ - Rimple Mehta; Linda Briskman; Michel Edenborough; Fran Gale; Samantha Tom Cherian; Mohammad Arif Nabizadah; Jasmina Bajraktarevic-Hayward; Asma Naurozi (Genealogy, 2025)
As numbers of displaced people throughout the world steadily increase with the rise in global conflicts, many Western nations, including Australia, increasingly thwart asylum-seeking and place harsh restrictions on entry. Nonetheless, Afghanistan’s troubled political history over several decades has generated steady movement of refugees to Australia, and Australia has offered protection, although often conditional and limited. Little is known about the experiences of women who fled, giving up their homes, professions, education, extended family, and social lives that were rich in connection. Despite expanding research and literature, there are still gaps in what is known about what happens to refugee women who resettle in Australia. The research outlined in this article uncovers the stories of six Afghan women, highlighting their agency to counter stereotypes. The article focuses not only on losses experienced, but ways in which this group of Hazara women negotiated their way in their new home of Australia, with the support of STARTTS, a not-for-profit organisation. Some of the initial barriers to resettlement in Australia involved accessible and timely information, limited proficiency in English, and comprehending laws and norms. The ongoing effects of trauma along with these barriers often accelerated the ageing process for these women, limiting their ability as well as opportunity for employment. These barriers were exacerbated in the context of the yearnings for their homeland and loved ones who were still in Afghanistan. Women were torn between feelings of gratitude for their own security and of guilt and pain for those in Afghanistan. Through STARTTS-facilitated groups, women found opportunities to connect with one another. They also used these connections to gather information about support programs, for themselves or their families, crucial for them to reconstruct their lives in Australia. For refugees experiencing dislocation, the formation of social networks in the host country contributes to belonging and connectedness and facilitates rebuilding trusting relationships that have been intentionally destroyed, where they can share their experiences in a safe, trauma-informed environment.